The 2019 Notice on Promoting the Systematic and Orderly Development of Commercial Carrier Rockets: The First Step Towards Regulating Private Space Activities in China. (August 2021) - Tronchetti, Fabio; Liu, Hao
Abstract: In June 2019, the Notice on the Promotion of a Systematic and Orderly Development of Commercial Carrier Rockets was issued. The enactment of the Notice represents an important moment in the development and management of the Chinese space program: on one side, it marks the first regulatory steps taken by Chinese authorities to govern the ongoing process of privatization of Chinese space activities, specifically the production and operation of private space launchers; on the other side, it constitutes the latest addition to the largely outdated corpus of Chinese space law. In this light of its significance, the purpose of this viewpoint is to discuss the Notice's background, highlight its positive features and shortcomings, and envision its expected impact on domestic space projects. Highlights: Private space activities are changing the nature of Chinese space activities. The 2019 Notice paves the way for the gradual expansion of Chinese national space law. The 2019 Notice is the first regulatory outcome of the privatization of Chinese space activities. The 2019 demonstrates the awareness of Chinese regulator on the need to upgrade existing Chinese space-related legislation.